Emerging diabetes therapies: Bringing back the β-cells - G. Basile; M.M.F. Qadir; F. Mauvais-Jarvis; A. Vetere; V. Shoba; A.E. Modell; R.L. Pastori; H.A. Russ; B.K. Wagner; J. Dominguez-Bendala (Elsevier, 2022)
Background: Stem cell therapies are finally coming of age as a viable alternative to pancreatic islet transplantation for the treatment of insulin-dependent diabetes. Several clinical trials using human embryonic stem cell (hESC)-derived β-like cells are currently underway, with encouraging preliminary results. Remaining challenges notwithstanding, these strategies are widely expected to reduce our reliance on human isolated islets for transplantation procedures, making cell therapies available to millions of diabetic patients. At the same time, advances in our understanding of pancreatic cell plasticity and the molecular mechanisms behind β-cell replication and regeneration have spawned a multitude of translational efforts aimed at inducing β-cell replenishment in situ through pharmacological means, thus circumventing the need for transplantation. Scope of Review: We discuss here the current state of the art in hESC transplantation, as well as the parallel quest to discover agents capable of either preserving the residual mass of β-cells or inducing their proliferation, transdifferentiation or differentiation from progenitor cells. Major Conclusions: Stem cell-based replacement therapies in the mold of islet transplantation are already around the corner, but a permanent cure for type 1 diabetes will likely require the endogenous regeneration of β-cells aided by interventions to restore the immune balance. The promise of current research avenues and a strong pipeline of clinical trials designed to tackle these challenges bode well for the realization of this goal.